New records of water mites (Acari: Hydrachnidia) from Tasmania, with descriptions of three new species - Pesic, Vladimir; Smit, Harry (Zootaxa, 2009)
Three new water mite (Acari: Hydrachnidia) species are described from Tasmania, Tasmanobates separatus sp. nov., Procorticacarus karanovici sp. nov. and Guineaxonopsis tasmanica sp. nov. The material was collected in 2008 during a biological survey by Tom and Ivana Karanović (Hobart, Tasmania) from surface and interstitial waters of Tasmania. Moreover, a detailed description of Litarachna cf. amnicola Cook, 1986 is given.